2014
DOI: 10.5455/jcme.20140619111139
|View full text |Cite
|
Sign up to set email alerts
|

Role play and #8211; an eff ective tool to teach clinical medicine

Abstract: Objective: This study was undertaken as an experimental effort to introduce role-play as a learning tool in teaching of clinical medicine, access its efficacy in understanding clinical scenarios and honing linguistic and examination skills through expression in medical students. The basic hypothesis was that, role-plays can guide the medical students in a better way by gaining knowledge and attitude to deal with real-life situations through simulation acts, so that they can apply this knowledge and skill gaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 9 publications
(17 reference statements)
1
33
0
Order By: Relevance
“…These parameters reflected the students' improved ability in remembering, recollecting and synthesizing pharmacological facts and its application in real-life situations (higher cognitive domain) and also their improved behaviour and communication towards patients (affective domain) after being sensitized to role-plays. These findings are similar to the results of the study conducted by Acharya S et al 6 Given the magnitude of the IHD problem and the need for prompt treatment, the medical management of IHD is a must know topic in pharmacology. As per the Knowles' principles of adult learning, students learn best when they are involved in the subject matter, when they have a need to know or when there is an internal motivation to learn.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These parameters reflected the students' improved ability in remembering, recollecting and synthesizing pharmacological facts and its application in real-life situations (higher cognitive domain) and also their improved behaviour and communication towards patients (affective domain) after being sensitized to role-plays. These findings are similar to the results of the study conducted by Acharya S et al 6 Given the magnitude of the IHD problem and the need for prompt treatment, the medical management of IHD is a must know topic in pharmacology. As per the Knowles' principles of adult learning, students learn best when they are involved in the subject matter, when they have a need to know or when there is an internal motivation to learn.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies conducted in medical students have demonstrated the effectiveness of role-play in teaching technical and communication skills in medical education. 6,7,10,11 In our study, we used the peer-role play technique that involved all the students to perform, learn and to personally experience patient concerns in front of their peers. Continuous feedback from peers gave the students an opportunity to sharpen their communication skills in a safe and supportive classroom environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations